Theory Implementation of Need for Help Wiedenbach and Self Care Orem in Pregnancy Case with Tuberculosis Multi Drug Resistance - Kusila Devia Rahayu; Setyowati S (Journal of Maternity Care and Reproductive Health, 2018)
Pregnancy with tuberculosis is classified as pregnancies with medical complicated non obstetrical and gynecological. Pregnancy with tuberculosis multi drug resistance occur in women who have a history of non compliance of treatment or treatment failure. Pregnancy with infection of mycobacterium tuberculosis multi drug resistance can cause  pregnancy disturbance and fetal development disorder in the form of premature delivery and low birth weight. Five cases of pregnancy with tuberculosis multi drug resistance in this case study has been getting nursing care by applying the theory of need for help wiedenbach in the acute phase and self care Orem in the maintenance phase. The application of nursing theory proved to meet immediate relief needs and promote self-care potential clients so that interruption of pregnancy can be overcome and preterm delivery did not occur. Specialist of maternity nursing have an important role in the management of nursing care of  pregnancies with complicated, therefore maternity nurses need to improve the knowledge and clinical skills on an ongoing basis. Keywords: Multidrug resistance, Self-care, Tuberculosis, Wiedenbach